Thermal and Dynamical Characteristics of Landfalling Severe Typhoons in South China against Different Monsoon Backgrounds - Zhixiang Xiao; Cai Yao (Atmosphere, 2023)
The characteristics of landfalling severe typhoons (LSTYs)—i.e., typhoons with landfall intensities of 2 min with a mean maximum sustained wind ≥41.5 m s−1—in South China (SC) were here examined. Thirteen LSTYs have been recorded in SC since 1949, and most of them underwent a rapid intensification before landfall. The LSTYs were classified into three categories based on the intensity of the western North Pacific summer monsoon, i.e., as weak, moderate, and strong monsoons. The characteristics of the three types of LSTYs are markedly different. Two LSTYs (7317 and 1523) were developed against a weak monsoon (WM) background and did not have abundant monsoon water vapor drawn into the typhoon cores. Therefore, these two LSTYs exhibited smaller horizontal outer sizes and weaker “warm–wet” cores than those in moderate and strong monsoons. However, a warm offshore ocean supplied a sufficient amount of energy, favoring these two LSTYs’ rapid intensification before landfall. There have been five LSTYs (9113, 0518, 0816, 1320, and 1826) that formed under strong monsoon (SM) conditions but obtained a poor energy supply from the coastal ocean. Embedded in the SM, the vigorous warm–wet monsoon flow was drawn into the typhoons and persisted for several days until landfall. Then, the five LSTYs developed strongly at the greatest horizontal scale and were maintained as severe typhoons for almost 48 h before landfall. The beneficial warm–wet atmospheric circulation stimulated the strongest warm (wet) core at the upper (lower) level of the LSTYs, and a secondary, low-level warm core occurred as well. In moderate monsoon (MM) cases (8106, 9617, 1311, 1410, 1418, and 1714), the strength of the monsoon flow, the “warm–wet” core of the typhoon, and the ocean energy supply were ranked just between those of the LSTYs in WMs and SMs. The development of the LSTYs in the MM cases resulted from a combination of the effects of monsoon and ocean energy supply. In addition, the powerful upper-level divergence ascribed to the strong South Asia High may have played an auxiliary role in MM cases. From the perspective of the sea surface temperature (SST) response to the LSTYs, because of a relatively fast translation speed and the warmer subsurface ocean, the SST cooling was weakest for WM cases. However, the strongest SST cooling was found in SM cases and it was partially due to their slowest translation speed.